Ograniczanie praktyk religijnych i rugowanie wartości chrześcijańskich z życia uczniów i ich rodzin przez władze oświatowe w okresie Polskiej Rzeczpospolitej Ludowej. Wspomnienia nauczycieli (Przegląd Religioznawczy – The Religious Studies Review, 2019)
The aim of the article is showing the ways of limitations of the religious practices and disposal of christianity values in the pupils’ and their families’ life in the process of creating the new, socialist man. The article is based on the interviews with teachers who worked in Polish Peoples’ Republic period. The critical analysis of sources and a free form of interview are used in the text. The communist authorities in Poland made a huge effort to create a new socialist society. Particularly they insisted on the teachers and the staff of education on each level. Moreover, the Marxism and Leninism became a base of educational and methodological attitude to the world. The material and scientists’ worldwide was a main background and it was in contradiction to religious practices and the Catholic faith represented by the students and their families. That’s why the communist goverment focused on spotlighting the nonclerical aspects of the Polish history. What it is more, the communist propoaganda “exposed” the recreational role of Catholic Church in Poland.